Advanced Glycation End-Product-Modified Heat Shock Protein 90 May Be Associated with Urinary Stones - Takanobu Takata; Shinya Inoue; Kenshiro Kunii; Togen Masauji; Junji Moriya; Yoshiharu Motoo; Katsuhito Miyazawa (Diseases)
Background: Urinary stones (urolithiasis) have been categorized as kidney stones (renal calculus), ureteric stones (ureteral calculus and ureterolith), bladder stones (bladder calculus), and urethral stones (urethral calculus); however, the mechanisms underlying their promotion and related injuries in glomerular and tubular cells remain unclear. Although lifestyle-related diseases (LSRDs) such as hyperglycemia, type 2 diabetic mellitus, non-alcoholic fatty liver disease/non-alcoholic steatohepatitis, and cardiovascular disease are risk factors for urolithiasis, the underlying mechanisms remain unclear. Recently, heat shock protein 90 (HSP90) on the membrane of HK-2 human proximal tubular epithelium cells has been associated with the adhesion of urinary stones and cytotoxicity. Further, HSP90 in human pancreatic and breast cells can be modified by various advanced glycation end-products (AGEs), thus affecting their function. Hypothesis 1: We hypothesized that HSP90s on/in human proximal tubular epithelium cells can be modified by various types of AGEs, and that they may affect their functions and it may be a key to reveal that LSRDs are associated with urolithiasis. Hypothesis 2: We considered the possibility that Japanese traditional medicines for urolithiasis may inhibit AGE generation. Of Choreito and Urocalun (the extract of Quercus salicina Blume/Quercus stenophylla Makino) used in the clinic, Choreito is a Kampo medicine, while Urocalun is a characteristic Japanese traditional medicine. As Urocalun contains quercetin, hesperidin, and p-hydroxy cinnamic acid, which can inhibit AGE generation, we hypothesized that Urocalun may inhibit the generation of AGE-modified HSP90s in human proximal tubular epithelium cells.